IoT-Based Smart Necklace for Goat Health Monitoring - Mohamad Napiah, Mohamad Farhan Izzuddin; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2022)
The Internet of Things is very helpful in smart agriculture, especially for the livestock sector. Difficulties of livestock monitoring such as health problems, feeding, presence and safety can be facilitated through monitoring via smartphones. Livestock such as goats needs breeders’ help, especially for sick goats. Therefore, this study aims to design a device for monitoring goats’ heart rate and body temperature. The smart necklace product for goats was developed according to the waterfall model guide, allowing the device to obtain heart rate readings and temperature sensors using the Blynk app. It was created using NodeMcu ESP8266, Oled Display, Temperature Sensor, and Particle Burst Sensor. A charging module is required to charge the 3.7 v Lithium Polymer LiPo Battery when the battery is low. Tests have been done on this product, functional and design asp, an, dl as expert validation. The findings show that there is a shortage of power sources that are 3.7 v lithium battery cannot support the function of the circuit for a long period. Therefore, 5v power source is required. Further studies need to be carried out to improve this product for commercialisation, including the design and ergonomic aspects of the goat body.